Sports biomechanics : reducing injury risk and improving sports performance - Bartlett, Roger; Bussey, Melanie (London : Routledge, 2012)
'When working with sports men and women, the biomechanist is faced with two apparently incompatible goals: reducing injury risk and improving sports performance. Now in a fully updated and revised edition, Sports Biomechanics introduces the fundamental principles that underpin our understanding of the biomechanics of both sports injury and performance, and explains how contemporary biomechanical science can be used to meet both of those goals simultaneously. The first four chapters of this book look closely at sports injury, including topics such as the properties of biological materials, mechanisms of injury occurrence, risk reduction, and the estimation of forces in biological structures. The last four chapters concentrate on the biomechanical enhancement of sports performance, including analytical techniques, statistical and mathematical modelling of sports movements, and the use of feedback to enhance sports performance. Drawing on the very latest empirical and epidemiological data, and including clear concise summaries, self test questions and guides to further reading in every chapter, this book is essential reading for all advanced undergraduate and postgraduate students with an interest in biomechanics, sports injury, sports medicine, physical therapy or performance analysis'--
Keywords: Sports -- Physiological aspects; Human mechanics; Sports injuries -- Prevention